DOES ARTIFICIAL INTELLIGENCE HELP WOMEN IN INTERNATIONAL ARBITRATION? - Magdalena Łągiewska (International Journal of Law in Changing World, 2025)
New technologies are transforming international arbitration, with institutions adopting digital tools and case management systems to streamline proceedings. Artificial Intelligence (AI), in particular, is reshaping the field by introducing innovation-driven solutions that enhance efficiency. This article explores AI’s role in international arbitration, focusing on its potential to improve gender diversity in the appointment of arbitrators. Specifically, it examines whether AI-based selection tools can reduce discrimination and challenge entrenched stereotypes, such as the dominance of the “male, pale, and stale” profile in arbitral tribunals. The study suggests that AI could mark a turning point by promoting more inclusive selection processes. However, this potential hinges on the development of unbiased, well-programmed AI systems. While AI offers a promising path toward increasing diversity, its effectiveness will depend on its ability to avoid replicating existing biases and ensure fairness in the selection and appointment of women arbitrators.